Antiviral and cytotoxic activities of some plants used in Malaysian indigenous medicine - Ali, Abdul Manaf; Mackeen, Muhammad Mukram; El-Sharkawy, Saleh H.; Abdul Hamid, Junainah; Ismail, Nor Hardiani; Ahmad, Faujan; Lajis, Md Nordin (Universiti Putra Malaysia Press, 1996)
Ethanolic extracts of 61 medicinal plants used in Malaysia were screened for antiviral and cytotoxic activities. Antiviral activity was tested against the herpes simplex type-1 (HSV-1) and vesicular stomatitis (VSV) viruses, and cytotoxicity was assayed using the HeLa cell line. Antiviral activity against both viruses was present in the extracts from Calotropis gigantea, Costus speciosus, Eugenia michelii, Hedyotis auricularia, Mentha arvensis, Orthosiphon aristatus, Polygonum minus and Ricinus communis (MIG: 0.002-0.1 mg/ml). The extracts from Alternanthera sessilis, Blumea chinensis, Eleusine indica, Euphorbia hirta, Freycinetia malaccensis, Leea indica and Solanum americanum were active in selectively inhibiting HSV-1 (0.001-0.1 mg/ml). Selective activity against VSV was shown by the extracts from Acalypha indica, Bertholletia excelsa, Cerbera manghas, Codiaeum variegatum, Plectranthus amboinicus, Centella asiatica, Mirabilis jalapa, Morinda elliptica, Oenanthe javanica, Piper sarmentosum and Premna odorata (MIG: 0.005-0.1 mg/ml). Gytotoxic activity was present in the extracts from Acalypha indica, Andrographis paniculata, Cerbera manghas, Codiaeum variegatum, Cosmos caudatus, Elephantopus scaber, Etlingera elatior, Eugenia michelii, Freycinetia malaccensis, Hibiscus rosa-sinensis,Cen~ella asiati~a, Lecythis ollaria, Mentha arvensis, Mirabilis jalapa, Morinda elliptica, Ocimum tenUlflorum, PIper sarmentosum and Polygonum minus (CD50: 0.001-0.1 mgjml).Co-existing antiviral and cytotoxic activities were shown by Eugenia michelii, Mentha arvensis and Polygonum minus.